Development and testing of a new tick-borne encephalitis virus vaccine candidate for veterinary use - Salát, Jiří; Formanová, Petra; Huňady, Milan; Eyer, Luděk; Palus, Martin; Ruzek, Daniel (Vaccine, 2018)
In tick-borne encephalitis (TBE) endemic areas, consumption of unpasteurized milk or milk products from grazing domestic ruminants (goats, cattle, and sheep) represents a risk of TBE virus (TBEV) infection for humans. In addition to vaccination of humans, human alimentary TBEV infections can be avoided by pasteurizing milk or by vaccination of the ruminants. However, there is presently no TBEV vaccine for veterinary use. Here, we developed a new veterinary TBE vaccine candidate based on cell culture-derived, purified, and formaldehyde-inactivated TBEV (strain Hypr). The safety and immunogenicity of the vaccine was evaluated in mice and sheep and was well-tolerated while eliciting the production of high levels of virus-neutralizing antibodies. Vaccination provided full protection against lethal TBE in mice, prevented development of viremia in sheep and presence of TBEV in milk of lactating ewes. This vaccine is a good candidate for immunization of ruminants to prevent alimentary milk-borne TBEV infections in humans.
Keywords: RNA, Viral; neutralizující protilátky; RNA virová; polymerázová řetězová reakce; Formaldehyde; Male; protilátky virové; Vaccine; myši inbrední BALB C; buněčné kultury; Encephalitis Viruses, Tick-Borne; inaktivované vakcíny; mužské pohlaví; ovce; Sheep; Tick-borne encephalitis; Mice, Inbred BALB C; Encephalitis, Tick-Borne; Viral Vaccines; Lactation; Veterinary vaccine; formaldehyd; Animals; ženské pohlaví; zvířata; klíšťová encefalitida; Antibodies, Neutralizing; mléko; Cell Culture Techniques; myši; Antibodies, Viral; viry klíšťové encefalitidy; Polymerase Chain Reaction; laktace; Immunogenicity, Vaccine; Mice; Female; virové vakcíny; imunogenicita vakcíny; Alimentary infection; Milk; Vaccines, Inactivated